2020
DOI: 10.19166/nc.v7i2.2278
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Youtube to Develop Nursing Students’ Autonomous Learning and Listening Comprehension: An Experimental Study

Abstract: <p>Industrial Revolution (IR) 4.0. is about dealing with digital-native students  and developing autonomous learning. One possible strategy to deal with these issues is using YouTube as a tool for English language learning. There have been some studies discussing the effectiveness of using it, yet we still have niches; for instance, deeper and wider contexts and respondents. Thus, this study aims to examine students’ autonomy over their learning and whether YouTube can develop the listening comprehension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Promoting autonomous Pratiwi & Waluyo learning was significant in four categories of listening skills, but the students' learning outcomes improved insignificantly. This finding contrasts with the study of non-English major students in another Indonesian university, which significantly improved autonomous learning and students' learning outcomes (Recard et al, 2019). An experimental study in a Chinese university also showed that the learners were autonomous in their listening skills and significantly improved their learning outcomes (Guo, 2012).…”
Section: Discussioncontrasting
confidence: 77%
“…Promoting autonomous Pratiwi & Waluyo learning was significant in four categories of listening skills, but the students' learning outcomes improved insignificantly. This finding contrasts with the study of non-English major students in another Indonesian university, which significantly improved autonomous learning and students' learning outcomes (Recard et al, 2019). An experimental study in a Chinese university also showed that the learners were autonomous in their listening skills and significantly improved their learning outcomes (Guo, 2012).…”
Section: Discussioncontrasting
confidence: 77%